Geohistorical Structural Design Tables for the Building Stones of the Maltese Archipelago - Lino Bianco (Studia Historiae Scientiarum)
The engineering properties of building materials are essential knowledge when it comes to structural design. In 1885, the Crown Agents for the Colonies published a study on the resistance of Malta stone to cracking and crushing, in an attempt to develop stress design tables for local masonry. This article addresses the evolution of geological maps in the nineteenth century and, then, introduces the content of this publication. The geological formations described in the latest map are still used to this day. Finally, it discusses the usefulness of these tables in establishing the mechanical properties that Maltese stone can withstand. To identify the quality of the stone discussed in this publication, a geological map available at the time, namely that published by Andrew Leith Adams in 1870, which proved to be moderately accurate, was used. The testing procedures applied followed the accepted laboratory practice at the time. A retrospective analysis of the contents of this publication reveals that the results contained some mathematical errors.